Understanding value characteristics toward a robust IT governance application in private organizations using COBIT framework. (20th July 2017) - Alkhaldi, Firas M; Hammami, Samir Marwan; Ahmar Uddin, Mohammed
This research is an inquiry of Control Objectives for Information and Related Technologies (COBIT) as a high-level governance and control framework which was proposed by ITGI by providing incite and statistical evidence investigating whether ITGI pillars can be accounted for the same IT governance dimension. The data were collected via a questionnaire distributed to 40 private organizations in the Middle East, comprising a sample size of 179 respondents of strategic- and tactical-level managers. To investigate the research questions, the researchers apply an exploratory and confirmatory factor analyses using EQS 6.3 and SPSS 21. The findings of the research indicate that there is an awareness of the nature of the relationship that IT governance has with its various factors as suggested by the COBIT framework: business/IT alignment, IT value delivery, IT resource management, IT risk management and IT performance. The findings also revealed that "IT risk management" is the leading indicator in explaining the IT governance application behavior. The validated model of ITGOV shows that "IT business alignment" has the least significant impact on the study sample. The overall results illustrate the needs and the imperatives of the model factors in achieving a better understanding of the characteristic value of the ITGOV applications using the COBIT framework as suggested by ITGI.